PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF DIGITAL COMPETENCE OF FUTURE SKILLED WORKERS IN THE SERVICE SECTOR (Innovative professional education, 2025)
One of the priority areas of development of the Ukrainian state is the construction of a development-oriented and people-oriented digital society and, accordingly, updating the content of training future qualified workers capable of using digital technologies in the learning process, as well as in future professional activities. Currently, the professional training of future qualified service workers is accompanied by the active use of digital tools in the application of methods and modern pedagogical and production technologies, and the innovative development of restaurant establishments, in particular regarding the digitalization of individual service functions, indicates the need to develop digital competencies in future qualified service workers.
Keywords: pedagogical conditions, information technologies, information technologies for training, vocational (vocational and technical) education institution, future qualified service sector workers